Pengembangan E-Modul Menggunakan Flip PDF Professional Pada Mata Pelajaran IPS Kelas V SD - Ayunda Mizani; Syaiful Marwan (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The aim of this research is to find out how to create an electronic header using Flip PDF Professional software. The limited availability of teaching materials in schools causes this problem. Apart from that, e-modules are not technically used as teaching materials by educators. Apart from that, because teachers have not created their own e-module-based teaching materials, learning only depends on textbooks. Researchers carry out research and development (R&D) or development using a four-stage development version, which consists of defining, designing, development (developing), and dissemination (disseminating). This research uses validity and practicality test sheets. The study shows that the product is an e-module that uses a professional PDF flip. The validation results of the E-module show that it is very feasible in terms of appropriateness of content, media, and language. An average score of 87% is categorized as very appropriate in terms of language eligibility. Apart from that, 96% of students and 95% of teachers stated that the E-module could be used as teaching material for reading the proclamation text for class V UPT SDN 23 Cubadak.